2006
DOI: 10.3748/wjg.v12.i23.3716
|View full text |Cite
|
Sign up to set email alerts
|

Activation and dramatically increased cytolytic activity of tumor specific T lymphocytes after radio-frequency ablation in patients with hepatocellular carcinoma and colorectal liver metastases

Abstract: to 0.109 (± 0.005) for CD4 + and 0.11 (± 0.012) for CD8 + T cells against HCC, and to 0.115 (± 0.031) for CD4 + and 0.15 (± 0.02) for CD8 + cells for colorectal metastases (P < 0.0001). No increased SI was observed with nonmalignant tumor tissue at all time points. Before RFA cytolytic activity against the respective cancer cells was low with 2.62 (± 0.37) relative luminescence units (RLU), but rose more than 100 fold 4 and 8 wk after RFA. Spontaneous release was < 2% of maximum release in all experiments. CON… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
84
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(89 citation statements)
references
References 32 publications
3
84
0
1
Order By: Relevance
“…Moreover, in several animal models [152,153,154,155] as well as in human primary [156,157,158] or secondary [156, 157] liver tumors, RFA can induce an antigen-specific T cell response. In a rabbit VX2 tumor model, RFA induced the presence of tumor-specific circulating T cells, as well as a dense peritumoral T cell infiltration [152].…”
Section: Oncological Arguments With Indirect Evidence Pro and Contra mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in several animal models [152,153,154,155] as well as in human primary [156,157,158] or secondary [156, 157] liver tumors, RFA can induce an antigen-specific T cell response. In a rabbit VX2 tumor model, RFA induced the presence of tumor-specific circulating T cells, as well as a dense peritumoral T cell infiltration [152].…”
Section: Oncological Arguments With Indirect Evidence Pro and Contra mentioning
confidence: 99%
“…RFA in 20 patients with primary or secondary liver tumors was shown to induce tumor-antigen-specific CD8+ T lymphocytes in some patients from 3 months on after treatment [156]. In a study with 6 patients with HCC and 6 patients with CRLM, RFA induced a tumor-specific cytotoxic T cell stimulation with a dramatically increased tumor-specific cytolytic activity of CD8+ T cells [157]. Post-RFA necrotic tumor debris has been shown to stimulate the antigen-presenting dendritic cells, which play a pivotal role in the induction of immunity [160,161,162].…”
Section: Oncological Arguments With Indirect Evidence Pro and Contra mentioning
confidence: 99%
“…In humans, RFA treatment can exert modulatory effects on the immune system (22) and could boost lymphocyte proliferation and production of inflammatory cytokines in response to tumor extracts in HCC patients (10,11). Herein, we show for the first time that in metastatic cancer patients, RFA treatment can amplify the specific T cell response against an epithelial tumor antigen such as the MUC1 Oglycoprotein.…”
Section: Discussionmentioning
confidence: 83%
“…Recent reports have also shown that the in vitro proliferative response to tumor extracts is amplified in HCC patients following RFA (10,11), although RFA impacts on important parameters of biological tumor behaviour such as metastatic spreading and viral load are still unclear (12). So far, little is known about the effect of RFA treatment on the immune response in metastatic cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…Although it has been postulated that RFA decreases intimal hyperplasia [6], this does not explain increased survival in the absence of increased stent patency. Hänsler et al [7] reported in a study of 10 patients with primary or secondary liver tumors undergoing RFA increased cytologic tumorspecific T cell stimulation suggestive of an immunological mechanism for increased survival. den Brok et al [8] also reported increased immune response to RFA in a mouse model, suggesting that immune activation by RFA may enhance tumor suppression.…”
mentioning
confidence: 99%